Optimization of gelatin extraction from Thai fish panga (Pangasius bocourti sauvage) skin - Trakul Prommajak (2018)
An investigation on optimal conditions for gelatin extraction from the Thai fish panga (Pangasius bocourti Sauvage) skin was performed by response surface methodology. A Box-Behnken design was applied to examine the effects of extraction temperature (40-70°C), pH (3.7-7.4) and extraction time (1-5 h) on gelatin yield, gel strength and gel colour. All regression models were significant (P≤0.01) and lack-of-fit of the models was insignificant, except for that of the gel strength. The Anderson-Darling normality test of the standardized residuals showed adequacy of all models. The optimal conditions for gelatin extraction were at 55°C, pH 4.55 for 1 h. The predicted responses were 20.22% gelatin yield, 506.55 g gel strength, 42.22 lightness (L*), 3.56 chroma (C*) and 43.35° hue angle (h°). The experimental responses of gelatin extracted at the optimal conditions were not significantly different (P>0.5) from the predicted value.